The casting process and high temperature oxidation resistance of high chromium cast iron grate bar - Zhiru, Chen (Array, 2019)
The solidification process of a high chromium cast iron grate bar used for sinter machine was simulated, and high temperature oxidation resistance was also investigated. The simulation result shows that sequence solidification can be achieved and no shrinkage cavity and porosity were observed. Based on the analysis of the microstructure, it could be known that the grate bar was well protected by the Fe3O4、Fe2O3 and Cr2O3 oxide films at temperatures lower than 800°C.